Communicating Across Cultures and Languages in the Health Care Setting Voices of Care - Penn, Claire (Communicating in Professions and Organizations, 2018)
This book offers a novel approach to understanding the complexities of communication in culturally and linguistically diverse health care contexts. It marks the culmination of two decades of research in South Africa, a context that has obvious application in a wider international climate given current globalization and migration trends. The authors draw from a large body of evidence based across different sites and illnesses, scrutinising both the language dynamics of intercultural health interactions and the perceptions and narratives of multiple participants. Including a range of theoretical, methodological and empirical considerations, the volume sheds light upon qualitative research methods and their application in the intercultural context. This book will be a valuable resource for health professionals, medical educators and language practitioners as well as students and scholars of discourse analysis and the medical humanities.